De novo a data e o local de nascimento de Afonso I - Abel Estefânio (Medievalista)
Whatever the place where Afonso Henriques was born, our knowledge about its historical importance remains the same. It is just a mere biographical formality. However, the investigation of this detail in the scientific field may be important for a biography of his parents. Implying a thorough examination of the actual itinerary of Count Henry and Teresa, surely that will help to better understand their political role in an environment dominated by a succession crisis. The documentation of Sahagún Monastery has brought an unexpected and decisive contribution to this study, while opening the possibility of our first king having been born in the court of León-Castilla.